2014
DOI: 10.1002/ange.201308843
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Light‐Mediated Imaging of Latent Fingerprints based on Molecular Recognition

Abstract: Photoluminescence is one of the most sensitive techniques for fingerprint detection, but it also suffers from background fluorescence and selectivity at the expense of generality. The method described herein integrates the advantages of near-infrared-light-mediated imaging and molecular recognition. In principle, upconversion nanoparticles (UCNPs) functionalized with a lysozyme-binding aptamer were used to detect fingerprints through recognizing lysozyme in the fingerprint ridges. UCNPs possess the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 51 publications
(18 reference statements)
0
61
0
Order By: Relevance
“…The minimally detectable cocaine loaded was calculated as 90 ng. Yuan et al [75] employed upconversion NPs (UCNPs) functionalized with aptamers for the detection of fingerprints through recognizing lysozyme. The fingerprints treated with UCNPs/ aptamer conjugates displayed a better luminescence image than those treated with fluorescein or CdTe QDs, due to the ability of UCNPs to suppress background fluorescence.…”
Section: Aptamer-based Reagentsmentioning
confidence: 99%
“…The minimally detectable cocaine loaded was calculated as 90 ng. Yuan et al [75] employed upconversion NPs (UCNPs) functionalized with aptamers for the detection of fingerprints through recognizing lysozyme. The fingerprints treated with UCNPs/ aptamer conjugates displayed a better luminescence image than those treated with fluorescein or CdTe QDs, due to the ability of UCNPs to suppress background fluorescence.…”
Section: Aptamer-based Reagentsmentioning
confidence: 99%
“…Since the first demonstration of UCL bioassay in 1999 [182], there has been an extensive research on Ln 3+ -doped UCNPs in various bioassay applications [183][184][185][186]. One representative paradigm was reported by Tanke and coworkers [187], who employed Y 2 O 2 S : Yb,Er submicrons as UCL probes in DNA microarrays for the detection of nucleic acid hybrids.…”
Section: Upconverting Luminescent Bioassaymentioning
confidence: 99%
“…721 Among different NPs being studied so far, UCNPs are being considered as ideal probes for developing the latent fingerprints. 22 UCNPs can convert radiation of long wavelength (e.g., near-infrared (NIR) light) into emissions of shorter wavelength (e.g., visible light) via a two-photon or multiphoton mechanism. 2332 They are excited by NIR light to emit strong visible fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Wang et al reported the use of a solution of NaYF 4 :Yb,Er UCNPs functionalized with lysozyme-binding aptamer for recognizing the lysozyme in the sweat associated with the fingerprints for the detection of fingerprints. 22 However, this method contained complicated steps and was not practical at crime scenes because it required chemical modification of the large UCNPs (~260 nm) through tedious procedures and long-time incubation of fingerprints with the UCNPs solution for 30 min.…”
Section: Introductionmentioning
confidence: 99%